The Influence of Corporate Environmental Ethics on Competitive Advantage: The Mediation Role of Green Innovation - Chang, Ching-Hsun (2011)
This study utilizes structural equation modeling (SEM) to explore the positive effect of corporate environmental ethics on competitive advantage in the Taiwanese manufacturing industry via the mediator: green innovation performance. This study divides green innovation into green product innovation and green process innovation. The empirical results show that corporate environmental ethics positively affects green product innovation and green process innovation. In addition, this study verifies that green product innovation mediates the positive relationship between corporate environmental ethics and competitive advantage, but green process innovation does not. Therefore, corporate environmental ethics can not only affect competitive advantage directly, but also influence it indirectly via green product innovation in the Taiwanese manufacturing industry. Taiwanese manufacturing companies can increase their corporate environmental ethics and green product innovation to enhance their competitive advantages.
Keywords: Competitive Advantage; Green process innovation; green product innovation; Corporate environmental ethics